Effect of impact load and active load on bone metabolism and body composition of adolescent athletes - Lima, F.; de Falco, V.; Baima, J.; Carazzaio, G.; Pereira, R. M. (Medicine & Science in Sports & Exercise, 2001)
Purpose: It is unclear whether adolescents involved in nonweight-bearing activities experience a delay in bone growth acquisition and sexual maturation. The purpose of this study was to compare bone mineral density (BMD), body composition, hormonal profile, and bone biochemical markers of adolescent athletes active in sports involved in impact load sports with those participating in active load sports. Methods: Forty-five male Caucasian athletes aged 12-18 yr were divided into two groups according to type of skeleton loading, impact (N = 18), or active (N = 27). Twenty-four male Caucasian adolescents (12-18 yr) served as controls and only performed the activities included in their physical education classes. All subjects were assessed for bone mass, body composition, and bone age by dual x-ray absorptiometry (DXA). Serum calcium (Ca), phosphorus (P), bone-specific alkaline phosphatase (BAP), total testosterone, FSH, LH, urinary calcium to creatinine ratio (Ca/Cr), and urinary deoxypyridinoline crosslinks to creatinine ratio (DPD/Cr) were measured. Results: The impact load group presented the highest BMD among the three groups for all studied sites. Lean mass and absolute weight were correlated with all of the bone mass measurements. BAP levels were significantly higher and testosterone levels significantly lower in the active load group compared with the impact group. Conclusion: High-impact load exercises have a beneficial effect on bone mass in male adolescents. There is also a positive correlation of weight and body composition with BMD. However, further longitudinal studies are necessary to determine whether there is a delay in bone growth acquisition among adolescents involved in a nonweight-bearing exercise regimen and its association with sex hormones.